1992
DOI: 10.1080/00288330.1992.9516500
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact of trawling on the seabed: A review

Abstract: Fishers have been complaining about the effects of bottom trawl gear on the marine environment since at least the 14th century. Trawl gear affects the environment in both direct and indirect ways. Direct effects include scraping and ploughing of the substrate, sediment resuspension, destruction of benthos, and dumping of processing waste. Indirect effects include post-fishing mortality and long-term trawl-induced changes to the benthos. There are few conclusive studies linking trawling to observed environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
246
0
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(259 citation statements)
references
References 34 publications
4
246
0
9
Order By: Relevance
“…Hutchings 1990, Jones 1992, Auster et al 1996, Collie et al 1997, Jennings & Kaiser 1998. These studies have demonstrated a variety of trawling impacts: direct impacts on the benthic fauna and substrate, and secondary impacts, particularly on fishes, arising from reduced cover and habitat complexity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hutchings 1990, Jones 1992, Auster et al 1996, Collie et al 1997, Jennings & Kaiser 1998. These studies have demonstrated a variety of trawling impacts: direct impacts on the benthic fauna and substrate, and secondary impacts, particularly on fishes, arising from reduced cover and habitat complexity.…”
Section: Discussionmentioning
confidence: 99%
“…A rapidly growing literature has shown that trawling may substantially alter marine benthic habitats and communities (Bradstock & Gordon 1983, de Groot 1984, Sainsbury 1988, Hutchings 1990, Jones 1992, Auster et al 1996, Collie et al 1997. Several studies have also demonstrated significant secondary, or indirect, impacts on elements of the community, such as juvenile or adult fishes, that utilize biogenic structures on the seafloor directly impacted by trawling (Bradstock & Gordon 1983, Sainsbury 1988.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the susceptibility of benthic communities and habitat integrity to perturbation associated with bottom fishing activity has long been established (Thrush and Dayton 2002;Jones 1992), evaluations of the longer term effects of restructured post-disturbance communities inhabiting altered sedimentary conditions on biogeochemical processes have been less prominent (Lambert et al 2014). Cohesive shelf sediments have been considered to be particularly important areas for biogeochemical activity owing to the presence of elevated concentrations of organic matter and living biomass, contributing an estimated 44% of global denitrification and [40% of total organic matter burial (Muller-Karger et al 2005;Seitzinger et al 2006;Middleburg and Levin 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Los arrastres de fondo marino con una zona de perturbaciĂłn de 120-150 cm de ancho y una profundidad de 5 cm, ocasionan un detrimento de la biota marina (Jones, 1992;Engel y Kvitek, 1998;Hall, 1999) afectando directamente la abundancia e indirectamente las estructuras y organismos que sirven de hĂĄbitat y alimentaciĂłn, respectivamente (Sainsbury, 1988;Hall, 1999). A pesar de estas preocupaciones, la intensidad y eficacia de la pesca de arrastre de fondo han aumentado en todo el mundo (Hall, 1999).…”
Section: Introductionunclassified
“…Los estudios realizados sobre el impacto de la pesca de arrastre en los diversos componentes del ecosistema marino, han encontrado resultados mixtos y con ello se demuestra que los efectos de la pesca de arrastre sobre el bentos no es una tarea fĂĄcil de investigar por razones diversas. Los daños causados en el ecosistema marino varĂ­an en funciĂłn del sistema de pesca de arrastre, las artes (tipo, configuraciĂłn y peso), el tipo de sedimento y biota, y las perturbaciones naturales (Jones, 1992;Kaiser y Spencer, 1996).…”
Section: Introductionunclassified